Thermal Hydraulic Modeling of Once-Through Steam Generator by Two-Fluid U-Tube Steam Generator Code - A. Zeighami; M. Rahgoshay; M. Khaleghi; M. Hashemi-Tilehnoee (Atom Indonesia, 2017)
The THERMIT U-tube steam generator (THERMIT-UTSG) code was used for evaluation for the parametric study of a scaled once-through pressurized water reactor steam generator (OTSG) made by Babcock & Wilcox. The results of the code were compared to the experimental data of the 19-tube OTSG and a simple heat transfer code that was developed by Osakabe. The main calculated thermodynamic parameters were primary-secondary fluid temperatures, tube wall internal and external temperatures that were subjected to primary and the secondary fluid, and the secondary fluid vapor quality. The assessed code can be used for modeling the OTSGs with some modification. The results of THERMIT-UTSG were in agreement with the experimental results and the prediction of Osakabe’s numerical model.